Analisis Pendapatan Nelayan dan Distribusi Pemasaran Ikan Cakalang di Kota Jayapura - Antonia Klara; Sarlota Arrang Ratang; Halomoan Hutajulu (Jurnal Manajemen dan Bisnis, 2019)
Resource of skipjack fish is one of the recovered natural resources found in Jayapura City and has the potential to be optimized in supporting regional development and efforts to improve community welfare. the utilization efforts so far still use a conventional approach that is oriented towards yield and number of catches. The purpose of the study was to understand the factors that influence the income of fishermen, and understand the marketing system of catching tuna fish in Jayapura City. Respondents researched 90 families using randomized stratification methods. The type of data used: primary data in the form of community income data, the number of fishermen's catches, the number and types of production costs, marketing systems, types and fishing equipment, social culture of the community. Secondary data are fisheries statistics, annual reports, Jayapura City in numbers. Data sources are DKP, BPS, Bappeda, Disperindagkop Kota Jayapura. The research analysis methods are Multiple Regression Analysis with the Smallest Squares Method (OLS) and Marketing System Analysis Methods. The results showed that the variable selling price, the number of catches, work experience, capital, age, education level and fishing gear had a significant influence on the income of fishermen. Determination Value R2 = 0.890. The results of various classical assumption tests indicate that the data normality test is very normal and residuals have spread normally.